The place of landscape symbolism in more-than-representational approaches: The place of landscape symbolism in more-than-representational approaches (Élisée - Revista de Geografia da UEG, 2025)
This epistemological article aims to evaluate the role of symbolisms within the more-than-representational approach. From the point of view of cultural approaches, more-than-representational epistemology presents itself as innovative because it is capable of transcending taken-for-granted symbolisms and detailing the meanings that are perpetually re-signified amidst the complex webs of human and non-human relations. As a strategy for evaluating symbolism in more-than-representational approaches, the article compares a brief history of cultural geographies that takes as its starting point the sauerian tradition and passes through the dominant approaches of the new cultural geography. The comparison of the place of symbolisms between these approaches highlights the epistemic differences and similarities, lending more clarity to the discussion.
Keywords: Representations; Symbolisms; Transcendences; Cultural Geography